Performance of polysulfone ultrafiltration membranes incorporating graphene oxide nanoparticles functionalized with different generations of poly(amido amine) - Ahmed T. Yasir (17302753) (2024)
Poly (amido amine) or PAMAM possesses an abundance of amine functional groups. The number of these hydrophilic groups increases exponentially with increasing PAMAM generation. Incorporating these hydrophilic functional groups can be an effective way to reduce the polysulfone membrane hydrophobicity and improve its permeation flux and its anti-fouling properties. In this work, different generations of PAMAM ranging from generation 0 to generation 4 were used to functionalize graphene oxide (GO) nanoparticles. GO-PAMAM nanocomposites synthesized by phase inversion method were incorporated in different synthesized polysulfone membranes matrices and the effect of GO-PAMAM nanoparticles of different PAMAM generations on performances of the modified polysulfone membranes was assessed. FTIR, analysis of the synthesized nanocomposites confirmed the presence of various amine groups on the surface of graphene oxide (GO), while XRD and Zeta potential analyses revealed reduced GO crystallinity and increased zeta potential values respectively. Membranes morphology analyses revealed that with increased PAMAM generation, synthesized membranes showed increased porosity, pore radius, increased hydrophilicity, and rougher surface. Permeability tests of the different membranes showed that polysulfone membrane incorporated with GO-PAMAM generation 4 nanocomposite exhibited 22-fold enhancement in pure water permeation flux and e > 99 % oil rejection with flux recovery rate of 75.6 %. For the same membrane, the percentage of nanomaterial leached from the nanocomposite after 30 days was only 4.24 %. Other Information Published in: Journal of Water Process Engineering License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jwpe.2024.105095